The effects of Kacip fatimah (Labisia pumila) extract on kidney, liver and uterus of white rat (Rattus norvegicus) - Abd Wahid, Mohd Effendy; Jaafar, Siti Nurtahirah; Z. M., Hussin; Lola, Muhammad Safiih; Saad, Mohd Zamri (Universiti Putra Malaysia Press, 2004)
Labisia pumila (Kacip fatimah) herb is well known to improve women health among traditional practitioners. The decoction from boiling Kacip fatimah is believed to hasten the delivery of baby during labour, and provide extra energy for women after birth. This study was conducted to determine the effect of the decoction from boiling extract of Labisia pumila on uterus of non-pregnant white rats (Rattus norvegicus). Eighteen clinically healthy rats were divided equally into two groups; Gp 1 as the control untreated, while Gp 2 was subjected to subcutaneous injection of the extract at 0.028 mg/kg. Three animals from each group were euthanized at day 1, 3 and 7 post-treatment. Serum was collected to determine the level of estrogen and progesterone using ELISA Estrogen and Progesterone Kit (Neogen Co.). Uterus were collected and fixed with 10% buffered formalin overnight before sectioned into 5 different sites at both left and right horn. Histological changes in the uterus were studied by Image Analyzer software. There was significant differences (p<0.05) in the thickness of endometrial wall, numbers and perimeter of endometrial glands in the treated group compared to others. No correlation (p>0.05) were noted in the level of serum estrogen and progesterone between all groups.